Integrated Radiology and Radiation Protection: The Physics of Optimizing Safety in the Era of 3D and 4D Imaging - Samsun, Samsun; Maryadi, Maryadi (Scientica Education Journal, 2024)
In the era of ever-evolving medical imaging technology, integrated radiology plays a vital role in improving diagnosis and therapy. The application of 3D and 4D technology in radiology has provided significant advances in terms of diagnostic accuracy and therapy planning. With the ability to produce clearer and more detailed images, doctors can make better decisions in patient care. However, the increasing use of radiation in medical imaging also raises serious concerns about the safety of both patients and medical personnel. This study aims to explore the importance of physics in optimizing radiation protection, as well as the challenges faced in integrating advanced technologies. We use a Systematic Literature Review (SLR) approach to identify best practices and recommendations that can be implemented to improve safety in the use of radiation. Through an analysis of existing literature, this study aims to provide insights into effective strategies in protecting patients from radiation risks without compromising imaging quality. Thus, this study will not only contribute to academic knowledge but will also benefit future clinical practice, ensuring the safety of patients and medical personnel in the era of high technology.